Functional Characterization of the EMBRYONIC FLOWER 2 Gene Involved in Flowering in Ginkgo biloba - Zhou, Xian; Wang, Lanlan; Yan, Janping; Ye, Jiabao; Cheng, Shuiyuan; Xu, Feng; Wang, Guiyuan; Zhang, Weiwei; Liao, Yongling; Liu, Xiaomeng (Frontiers in Plant Science, 2021)
Ginkgo biloba has edible, medicinal, and ornamental value. However, the long juvenile phase prevents the development of the G. biloba industry and there are few reports on the identification and functional analysis of genes regulating the flowering time of G. biloba. EMBRYONIC FLOWER 2 (EMF), an important protein in flower development, functions to promote vegetative growth and repress flowering. In this study, a novel EMF gene (GbEMF2) was cloned and characterized from G. biloba. GbEMF2 contains a 2,193bp open reading frame (ORF) encoding 730 amino acids. GbEMF2 harbors conserved VEF-Box domain by the plant EMF protein. Phylogenic analysis showed that GbEMF2 originated from a polycomb-group (Pc-G) protein ancestor and is a member of the EMF2 protein. qRT-PCR analysis revealed that GbEMF2 was expressed in all detected organs and at a significantly higher level in ovulate strobilus and microstrobilus than other organs. Overexpression of GbEMF2 driven by the CaMV 35S promoter in emf2 mutant Arabidopsis plants delayed flowering compared with emf2 mutant plants but earlier than wild-type (WT) plants, indicating that GbEMF2 repress flowering in G. biloba. Moreover, RNA-seq analysis of GbEMF2 transgenic Arabidopsis plants (GbEMF2-OE/emf2), WT plants, and emf2 mutants screened out 227 differentially expressed genes (DEGs). Among these DEGs, FLC, MAF5, and MAF5-1 genes were related to flower organ development and regulated by GbEMF2. In addition, some genes participating in sugar metabolism, such as AMY1, BAM1, and SUS3 genes, were also controlled by GbEMF2. Overall, our results suggested that GbEMF2 negatively regulates flowering development in G. biloba. This finding provided a foundation and target gene for shortening the Ginkgo juvenile period by genetic engineering technology.